Relation between Emotional Intelligence and Organizational Citizenship Behavior with Work Deviant Behaviors among Staff of Selected Hospitals in Tehran City - Mehdi Jafari Sirizi; Anvar Esmaili; Rahim Khodayari Zarnaq; Jalal Arabloo; Obeidollah Faraji (Tehran University of Medical Sciences, 2019)
Background: One of the main concerns of managers is work deviant behaviors of employees. Workplace deviance is voluntary behavior that violates significant norms and in so doing threatens the well-being of an organization, its members or both. The study aimed to explore the relationship between emotional intelligence and organizational citizenship behavior with work deviant behaviors.   Materials and Methods: This study was a cross-sectional descriptive analytical one. This study was conducted on 290 employees (administrative workers and nurses) working in four selected hospitals in Tehran city including Shahid Motahati, Shahid Rajaii, Hazrat-E-Rasol, and Dr. Shariati. Sampling method was stratified random sampling method. Data collection instruments were three questionnaires including Schutte's emotional intelligence, Padsakof organizational citizenship behavior, Bennett and Robinson's work deviant behavior. Validity and reliability of the questionnaires has already been verified in studies before. Data analysis was performed using independent T-test, ANOVA, Tukey and parametric Pearsonchr('39')s Correlation Coefficient.   Results: Among demographic and organizational variables, There was a significant relationship between age and work deviant behavior (P=0.012). Reverse significant statistical relationship between emotional intelligence, organizational citizenship behavior and courtesy with work deviant behavior was observed (P=0.0001).   Conclusion: The study results revealed that personnel with higher emotional intelligence will have a more positive attitude and more allegiance and commitment toward the organization; therefore they will show more organizational citizenship behavior and less inclined to abuse in the workplace.